2004
DOI: 10.1096/fj.04-2549fje
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane calcium ATPase deficiency causes neuronal pathology in the spinal cord: a potential mechanism for neurodegeneration in multiple sclerosis and spinal cord injury

Abstract: Dysfunction and death of spinal cord neurons are critical determinants of neurological deficits in various pathological conditions, including multiple sclerosis (MS) and spinal cord injury. Yet, the molecular mechanisms underlying neuronal/axonal damage remain undefined. Our previous studies raised the possibility that a decrease in the levels of plasma membrane calcium ATPase isoform 2 (PMCA2), a major pump extruding calcium from neurons, promotes neuronal pathology in the spinal cord during experimental auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 52 publications
2
78
0
Order By: Relevance
“…Inhibition of all PMCA activity by addition of 5(6)-carboxyeosin to pure neuronal cultures leads to cell death. This is preceded by a delay in the clearance of depolarization-induced calcium transients, neuritic damage and induction of activated caspase-3 [3] . These studies also indicated that most spinal cord neurons are dependent on PMCA activity for the effective clearance of depolarization-induced calcium transients, in vitro.…”
Section: In Vitro and In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of all PMCA activity by addition of 5(6)-carboxyeosin to pure neuronal cultures leads to cell death. This is preceded by a delay in the clearance of depolarization-induced calcium transients, neuritic damage and induction of activated caspase-3 [3] . These studies also indicated that most spinal cord neurons are dependent on PMCA activity for the effective clearance of depolarization-induced calcium transients, in vitro.…”
Section: In Vitro and In Vivomentioning
confidence: 99%
“…However, the activity of PMCAs can be modulated by a number of factors including calmodulin, phosphorylation by kinases, the protease calpain and caspases 1 and 3 [16] . The studies of Kurnellas et al [3] indicate that PMCAs are essential not only for the maintenance of basal calcium levels but also for the clearance of elevated intracellular calcium after stimulation or depolarization of spinal cord neurons. Other investigators have also reported that PMCAs contribute significantly to the removal of calcium from different neuronal subtypes in the retina and the dorsal root ganglia [17][18][19][20][21] .…”
Section: In Vitro and In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…PMCA2 −/− and PMCA2 +/+ mice were described previously [26]. For method optimization, normal C57BL/6 mice were used.…”
Section: Tissue Collection Protein Extraction and Itraq Labelingmentioning
confidence: 99%
“…(11) Other oxidants inactivate the plasma membrane calcium-ATPase, leading to increased levels of intracellular calcium [44][45][46][47][48]; such inactivation of the calcium ATPase has substantial pathophysiological effects [45][46][47][48] and may well contribute to the prolonged impairment of calcium extrusion seen under circumstances, where the NO/ONOO − cycle may have a role [49][50][51].…”
Section: �� �� ��Eci�c ������� − Cycle Mechanismsmentioning
confidence: 99%